Prevalence of Foreign Body as an Otorhinolaryngology Emergency at Tertiary Care Center of Central Nepal - Dhungana, Inclub; Rain, MD Kalammuddin; Pradhan, Ram Kumar (Med Phoenix, 2022)
Introduction: Ear, nose and throat foreign bodies are commonly encountered by otolaryngologists, pediatricians and primary care physicians mostly in emergency setup. The objective of this study is to find out the prevalence of aerodigestive and aural foreign bodies as an ENT emergency in tertiary care center of Central Nepal. Materials and Methods: This was a nine-month hospital based descriptive cross-sectional study performed in the Department of Ear, Nose and Throat (ENT) from June 2021 to March 2022 after approval from the Institutional Review Committee. Data was collected from emergency procedure record book and operation theatre register, entered and analyzed by using descriptive statistical methods. Results: Out of 300 cases presenting as an ENT emergency during the study time, 54 cases happened to be aerodigestive and aural foreign bodies which account for one-sixth of the ENT emergency case load, majority occurring in pediatric age group, and nasal foreign bodies being the most common type. Conclusion: We conclude from our study that foreign bodies in ENT mostly present as an emergency condition with more prevalence in pediatric population and they account for about one-sixth of the ENT cases presenting as an emergency.